Development and validation of stability-indicating RP-HPLC method for the simultaneous estimation of xylometazoline hydrochloride and ipratropium bromide from nasal spray dosage form - Bhaskar Musmade; Prashant Sanatan; Surbhi Lokhande; Shrikant Kulkarni; Shrinivas Bhope; Sriram Padmanabhan; Amol Pachpinde; Kishan Lohar (SpringerOpen, 2021)
Abstract Background A simple, robust, precise, and an accurate HPLC method was established for simultaneous estimation of xylometazoline hydrochloride and ipratropium bromide from a nasal spray dosage form. The effective separation was obtained by injecting 10 μl of sample and standard solutions on to an Inertsil ODS column, 250 × 4.6, mm, 5 μ at 45 °C using phosphate buffer with 1-pentane sulphonic acid sodium salt at pH 4.7 as a mobile phase A and acetonitrile as the mobile phase B. The gradient was optimized with a flow rate of 1 mL/min and a wavelength of 210.0 nm. Result The complete analytical method validation was successfully carried out as per ICH guidelines. The retrieval study was carried out at 50% to 150% level of working concentration, and results were in the range of 99 to 101% for both the analytes. The linearity was proven from 4 to 150% of working concentration with linear regression curve (R 2=0.999) for both the analytes. The developed method was robust for different parameters like column temperature, flow rate, mobile phase pH, composition, and gradient. Conclusion The developed HPLC method can be successfully used for the estimation of xylometazoline hydrochloride and ipratropium bromide from nasal spray dosage form as a release test in QC department of manufacturing units.